1995
DOI: 10.1111/j.1532-950x.1995.tb01306.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects of Longitudinal Division of the Corpus Callosum in Normal Dogs

Abstract: Longitudinal division of the corpus callosum was performed in six normal beagles to determine surgical morbidity. The corpus callosum was divided sagittally on the midline and the effect on neurological function was determined. Five of six dogs were clinically normal within 14 days or less after surgery. One dog had persistent but improving clinical signs consistent with a forebrain disturbance at 30 days after surgery. Overall, minimal morbidity and no mortality was associated with this surgical procedure. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 8 publications
0
11
1
Order By: Relevance
“…To date, research reports of epilepsy surgery for dogs or cats are limited to experimental studies for corpus callosotomy on normal dogs ( 12 ) or for amygdalohippocampectomy on a feline limbic seizure model induced with kainic acid ( 31 ), and experimental studies ( 14 , 32 ) or a clinical trial ( 13 ) of neurostimulation (vagus nerve stimulation and deep brain stimulation) in dogs. However, a few, but very precious, case reports have been published in the veterinary field ( 18 21 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, research reports of epilepsy surgery for dogs or cats are limited to experimental studies for corpus callosotomy on normal dogs ( 12 ) or for amygdalohippocampectomy on a feline limbic seizure model induced with kainic acid ( 31 ), and experimental studies ( 14 , 32 ) or a clinical trial ( 13 ) of neurostimulation (vagus nerve stimulation and deep brain stimulation) in dogs. However, a few, but very precious, case reports have been published in the veterinary field ( 18 21 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey of research priorities for idiopathic epilepsy in dogs revealed that non-ASD management, including epilepsy surgery, is highly expected by dog owners, general practice veterinarians, and veterinary neurologists (11). However, research on epilepsy surgery in the veterinary field is generally limited to experimental studies, with the majority concerning neuromodulation (12)(13)(14)(15)(16)(17). There are some case reports regarding intracranial surgery in canine patients with seizures, but most of those lack modern imaging or electrodiagnostic evidence (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…The CCT surgical procedure in cats has not been reported in the veterinary literature. Therefore, we performed it based on reports in dogs ( 4 ) and humans ( 2 ). Although the incomplete dissection may be the cause of the residual seizures, most of the CC, including splenium, was clearly visualized and easily bisected compared with the authors' limited experience of CCT in dogs (unpublished information).…”
Section: Discussionmentioning
confidence: 99%
“…In veterinary medicine, the surgical procedure for CCT in normal dogs has been reported by Bagley et al in 1995 ( 4 ), and the effect of CCT for epilepsy had been experimentally studied in feline seizure models such as kindling between the 1960s and 1990s ( 5 8 ). However, its clinical application and therapeutic outcome has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Determination of seizure foci and surgical removal of these foci have not yet been adequately explored in veterinary patients to our knowledge. The surgical procedure has been successfully performed in dogs, but whether it is useful in a patient with uncontrolled seizures remains to be seen.…”
Section: Surgerymentioning
confidence: 99%